The LGBT Phenomenon from a Social and Legal Perspective in Indonesia - Erfita; Arisman (Journal Informatic, Education and Management (JIEM), 2026)
The LGBT (Lesbian, Gay, Bisexual, and Transgender) phenomenon in Indonesia has become a complex social and legal issue amidst globalization and technological advancements. This study aims to analyze the definition, causes, social impacts, and legal perspectives on this phenomenon within the context of Indonesian moral and cultural values. The method used is descriptive qualitative with a sociological and normative juridical approach through literature review and social theory. The results of the study indicate that promiscuity and LGBT emerged due to the influence of global culture, digital media, and weak character education. Socially, this phenomenon has led to a shift in moral values, an increase in deviant behavior, and the emergence of stigma and social conflict. Although the LGBT community is increasingly present in public spaces and social media, Indonesian society generally still rejects its existence because it is considered contrary to religious and cultural norms . In terms of law, LGBT behavior and promiscuity are not explicitly regulated in the law, but acts that violate morality can be prosecuted through Articles 281 and 292 of the Criminal Code, as well as Law No. 44 of 2008 concerning Pornography. The government is expected to strengthen regulations and moral education that balance individual rights and social order. Thus, the phenomenon of promiscuity and LGBT reflects the nation's moral challenges that require a balanced legal, social, and educational approach to align with the values ​​of Pancasila and Indonesia's cultural identity.